Ici commence le Brésil ! Géohistoire d’une frontière compliquée - Federico Ferretti (EchoGéo)
A new work by the Brazilian historian Carlo Romani gives an important contribution to the geo-historical construction of the border between Brazil and French Guiana, including its political importance and its impact on local society. We analyze this work in the light of the role played by French Geographers, namely Henri Coudreau, Élisée Reclus and Paul Vidal de la Blache, who participated, with very heterogeneous positions, in the 1897-1900 border dispute. Finally, we stress the effectiveness of these debates for the present problems of regional integration in the concerned territories.